2014
DOI: 10.1007/s13311-013-0243-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Marketed Antiepileptic Drugs and Placebo in the Human Photosensitivity Screening Protocol

Abstract: A study of epilepsy patients with a reproducible range of photoparoxysmal responses (PPR) (epileptiform discharges evoked by flashing lights) has been used as a "proofof-concept" trial to determine if novel potential antiepileptic drugs (AEDs) should proceed in development. The standard design for this trial requires a 3-day inpatient stay and is single-blind. We evaluated two marketed and effective AEDs-one narrow-spectrum [carbamazepine (CBZ)], and one broad-spectrum [levetiracetam (LEV)]-using a novel doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Several prior antiepileptic drugs (AEDs) have been developed using participants with a photoparoxysmal response (PPR) on electroencephalogram (EEG) to provide initial data on the drugs’ potential antiepileptic activity . Suppression of photic stimulation‐induced epileptiform activity in such individuals indicates an anticonvulsive effect of potential AEDs; trials using such participants have been conducted for lamotrigine, levetiracetam, and brivaracetam among others . As epileptic activity can be elicited at will and with precise timing in these participants, eliciting a PPR provides an ideal opportunity to explore time to onset of action of a drug.…”
Section: Introductionmentioning
confidence: 99%
“…Several prior antiepileptic drugs (AEDs) have been developed using participants with a photoparoxysmal response (PPR) on electroencephalogram (EEG) to provide initial data on the drugs’ potential antiepileptic activity . Suppression of photic stimulation‐induced epileptiform activity in such individuals indicates an anticonvulsive effect of potential AEDs; trials using such participants have been conducted for lamotrigine, levetiracetam, and brivaracetam among others . As epileptic activity can be elicited at will and with precise timing in these participants, eliciting a PPR provides an ideal opportunity to explore time to onset of action of a drug.…”
Section: Introductionmentioning
confidence: 99%
“…1 1. Apparent discrepancy in results of CBZ in the photosensitivity model-dose and formulation impact the effect of CBZ Binnie et al 2 found that CBZ produced a suppressive PPR (positive effect) in the photosensitivity model; yet recently, French et al 3 did not. The difference in conclusion reached likely can be explained by:…”
mentioning
confidence: 99%
“…(a) the formulation of CBZ used (CBZ liquid solution 2 and tablets 3 ) and by (b) the total time of IPS EEG recording post-dose.…”
mentioning
confidence: 99%
See 2 more Smart Citations